PEG Based Alternative Stimulants and the Effect on Latex Production and Physiology of 6 Years Old of Clone PB 260 - Sari Rahayu, Murni; ., Nurhayati; Tistama, Radite; Asbur, Yenni (International Journal of Engineering and Technology, 2018)
The objectives of this study is to study formulation of PEG based alternative stimulant to increase latex production and physiologically safe for clones PB 260. This research was conducted at Sungei Putih Research Center, Rubber Research Center, Deli Serdang Regency, Province of North Sumatera and PTPD Paya Pinang, Tebing Tinggi, North Sumatera. The study uses 6 year-old of rubber clone PB 260 to determine differences in some parameter such as production (g/p/s), inorganic phosphate, sucrose and thiol levels. The results showed that stimulants have significant effect on production (g/p/s) and inorganic phosphate. PEG applications can encourage increased production (g/p/s) and inorganic phosphate. The combination of stimulant and PEG has very significant effect on production (g/p/s) and inorganic phosphate.Â Â